Association between open or closed reduction and avascular necrosis in developmental dysplasia of the hip: A PRISMA-compliant meta-analysis of observational studies. Issue 29 (July 2016) - Wang, Ya-Jie; Yang, Fan; Wu, Qi-Jun; Pan, Shi-Nong; Li, Lian-Yong
Abstract: Background: The risk of avascular necrosis of the femoral head (AVN) after treatment of developmental dysplasia of the hip is associated with the method of reduction. Some authors have suggested that open reduction is a risk factor for AVN; however, this is controversial. To our knowledge, a quantitative comparison of the incidence of AVN between closed and open reduction has not been conducted. Methods: Published studies were identified by searching PubMed, EMBASE, and the Cochrane Library up to May, 2015, focusing on the incidence of AVN after closed or open reduction for developmental dysplasia of the hip in children aged <3 years. Patients were age-matched who were treated by either closed or open reduction, but without pelvic or femoral osteotomy. Two authors independently assessed eligibility and abstracted data. Discrepancies were discussed and resolved by consensus. We pooled the odds ratios (ORs) and 95% confidence intervals (95%CIs) from individual studies using a random-effects model and evaluated heterogeneity and publication bias. Results: Nine retrospective studies were included in this analysis. The pooled OR for comparing open reduction with closed reduction for all grades of AVN was 2.26 (95%CI = 1.21–4.22), with moderate heterogeneity ( I 2  = 44.7%, P  = 0.107). The pooled OR for grades II to IV AVN was 2.46 (95%CI = 0.93–6.51), with high heterogeneity ( I 2  = 69.6%, P  = 0.003). A significant association was also found for the further surgery between open and closed reduction, with a pooled OR of 0.30 (95%CI = 0.15–0.60) and moderate heterogeneity ( I 2  = 46.4%, P  = 0.133). No evidence of publication bias or significant heterogeneity between subgroups was detected by meta-regression analyses. Conclusion: Findings from this meta-analysis suggest that open reduction is a risk factor for the development of AVN compared with closed treatment. Future studies are warranted to investigate how open reduction combined with pelvis and/or femoral osteotomy affects the incidence of AVN. Abstract : Supplemental Digital Content is available in the text